Removal of both cationic and anionic contaminants by amphoteric starch. (15th March 2016) - Peng, Huanlong; Zhong, Songxiong; Lin, Qintie; Yao, Xiaosheng; Liang, Zhuoying; Yang, Muqun; Yin, Guangcai; Liu, Qianjun; He, Hongfei
Highlights: Amphoteric starch can resist strong shear. Phosphate group has a high buffering capacity for pH values. The flocculation efficiency of amphoteric starch is better than cationic starch. Abstract: A novel amphoteric starch incorporating quaternary ammonium and phosphate groups was applied to investigate the efficiency and mechanism of cationic and anionic contaminant treatment. Its flocculation abilities for kaolin suspension and copper-containing wastewater were evaluated by turbidity reduction and copper removal efficiency, respectively. And the kinetics of formation, breakage and subsequent re-formation of aggregates were monitored using a Photometric Dispersion Analyzer (PDA) and characterized by flocculation index (FI). The results showed that amphoteric starch possessed the advantages of being lower-dosages-consuming and being stronger in shear resistance than cationic starch, and exhibited a good flocculation efficiency over a wide pH range from 3.0 to 11.0.